2019
DOI: 10.1002/aoc.5362
|View full text |Cite
|
Sign up to set email alerts
|

A new copper complex on graphene oxide: A heterogeneous catalyst for N‐arylation and C‐H activation

Abstract: Graphene oxide supported Cu (II) ligand complex (GO@AP/L‐Cu) has been synthesized and characterized by FT‐IR, Raman, PXRD, UV–Visible, TGA, XPS, FESEM, TEM, EDAX, Elemental mapping, BET, CHNS and AAS analysis. The complex has been found to be efficient and reusable heterogeneous catalyst for the N‐arylation and C‐H activation reactions, both the catalytic reactions were found to be simple, cleaner and give high yields (~ 90%) of product. The catalyst can be easily filtered out from the reaction mixture and reu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…The peak at 1109 for C-N indicates the CG composite successfully modi ed with 8-HQ. (Agarwal et al, 2003;Mittal et al, 2020) The peaks at 525 cm-1 for the Cu-O bond show complex formation with dye and cotton. (Bhakare et al, 2021) The crystalline structure of the composite was examined by powder X-ray diffractometer (Shimadzu XRD-6100 using CuKα radiation=1.5405Å) with a scanning rate of 2° per min and 2 theta (θ) angle ranging from 20° to 80° at current 30.0 mA and voltage 40.0 kV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at 1109 for C-N indicates the CG composite successfully modi ed with 8-HQ. (Agarwal et al, 2003;Mittal et al, 2020) The peaks at 525 cm-1 for the Cu-O bond show complex formation with dye and cotton. (Bhakare et al, 2021) The crystalline structure of the composite was examined by powder X-ray diffractometer (Shimadzu XRD-6100 using CuKα radiation=1.5405Å) with a scanning rate of 2° per min and 2 theta (θ) angle ranging from 20° to 80° at current 30.0 mA and voltage 40.0 kV.…”
Section: Resultsmentioning
confidence: 99%
“…(Goswami et al, 2003) The curve for 2-methyl-8hyrdoxy quinoline shown in Figure 2a iii a characteristic peak at 1580 cm-1 corresponding to the C=N, the peak at 3250 cm -1 denoting the O-H vibrations and peaks in the range of 1416 cm -1 denoting the C-O vibrations. (Mittal et al, 2020)The curve for the CHG composite shown in Figure 2a iv denotes the characteristic peak at around 1683 cm -1 for the C=O vibrations, (Palaskar et al, 2021) peak in the range of 1575 cm -1 representing the C=C and C=N linkage. The peak at around 3300 cm -1 denotes the O-H vibrations.…”
Section: Resultsmentioning
confidence: 99%
“…2a), a sharp absorption peak is observed at ~ 230 nm related to the π → π* transitions of the C-C bonds 24 . A small shoulder peak around 325 nm is also attributed to the n → π* transitions of the C = O bonds 24 . For rGo (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GO loaded with Cu(II) ligand complex (GO@AP/L‐Cu) was applied as a reusable heterogeneous catalyst for Chan–Lam coupling reaction of aniline derivatives with a wide range of arylboronic acids in the presence of KOH as base at 100°C for the preparation of the corresponding products in high yields (Scheme 12). [ 61 ] The GO@AP/L‐Cu catalyst was synthesized in three steps: In the first step, GO was treated with (3‐aminopropyl)trimethoxysilane (APTMS) to yield GO@AP. In the second step, GO@AP was reacted with 3‐(hydroxy(phenyl)methyl)but‐3‐en‐2‐one as ligand to form Schiff base (GO@AP/L).…”
Section: Application Of Copper Modified Graphene Oxide Catalysts For Carbon‐nitrogen Bond Formationmentioning
confidence: 99%